Study of mechanical and metallurgical characterization of correlated aluminium hybrid metal matrix composites. (2021) - Boobesh Nathan, V.; Soundararajan, R.; Brainard Abraham, C.; Vinoth, E.; Narayanan, J.K.
Abstract: This work investigates the mechanical and metallurgical characterization of correlated Aluminium Hybrid Metal Matrix Composites (AHMMC's) in which aluminium is used as matrix with two reinforcement materials embedded and as it gained enhanced properties over virgin material. The Aluminium alloy 6061 was taken as the base material with varying reinforcement of x weight percentages (2, 4, 6 wt%) of Silicon Carbide (SiC) and fixed value of 3 wt% Zirconium Di-Oxide (ZrO2 ) for this present research work. The AHMMC's were fabricated by stir casting technique at a stirrer speed of 350 rpm for 5 min with the temperature of the melt being 740 °C and the prepared melt was poured immediately in the mould. The mechanical test results exposed that hardness, tensile strength, compressive strength, and impact energy increases with inflating the reinforcement weight percentages due to the presence of harder reinforcement particles. The metallurgical microscope results exposed that there was a good intermolecular bonding between the alloy and reinforcements is provided by its increased properties of the AHMMC's. X- Ray Diffraction (XRD) and Energy Dispersive x-ray Spectroscopy (EDAX) opinion confirms the presence of reinforcement particles in the fabricated AHMMC's and also conforms the presence of reinforcements and other inter metallic compound phases in the hybrid composites. It is also noted that higher AA6061 with 6 wt%SiC and 3 wt%ZrO2 hybrid composites had better properties than other combinations and this AHMMC'sis recommended for automobile component replacement.